Ramona the pest [compact disc, unabridged] - Cleary, Beverly (HarperCollins Audio, 2010)
Ramona embarks on her first day of kindergarten. It is supposed to be the greatest day of her life, but Ramona quickly learns school isn't all fun and games when she doesn't make any friends.